Fluorescent copper nanoparticles: recent advances in synthesis and applications for sensing metal ions. Issue 9 (16th February 2016) - Guo, Yongming; Cao, Fengpu; Lei, Xiaoling; Mang, Lianghong; Cheng, Shengjuan; Song, Jintong
Abstract : Fluorescent copper nanoparticles (F-CuNPs) have received considerable attention due to their attractive features. In this review, the fluorescence properties, fabrication strategies and applications for sensing several metal ions of various F-CuNPs are discussed. Abstract : Fluorescent copper nanoparticles (F-CuNPs) have received great attention due to their attractive features, such as water solubility, wide availability, ease of functionalization and good biocompatibility, and considerable efforts have been devoted to the preparation and applications of F-CuNPs. This review article comprises three main parts. In the first part, we briefly present the fluorescence properties of F-CuNPs. Then we cover the fabrication strategies of various F-CuNPs functionalized by different ligands. In the third part, we focus on the applications of F-CuNPs for sensing metal ions, including Hg 2+, Pb 2+, Cu 2+, Fe 3+ and other metal ions. Lastly, we further discuss the opportunities and challenges of F-CuNPs in the synthetic strategies and applications for sensing metal ions.